Correlation between blood lipids and risk of thyroid nodules in euthyroid women - Lu LI; Qianyue ZHANG; Houfa GENG; Fangfang ZENG; Huaidong SONG (Zhongguo Linchuang Yixue)
ObjectiveTo explore the correlation and dose-response relationship between blood lipid parameters and the risk of thyroid nodules (TNs) in euthyroid women, providing references for disease prevention. MethodsA case-control study was conducted, including 1 412 euthyroid women (701 in the case group and 711 in the control group). Crude and multivariable logistic regression models were used to assess the association between blood lipid parameters and the risk of TNs, and restricted cubic spline regression was applied to explore the dose-response relationship. ResultsCompared with women in the lowest quartile of serum triglyceride (TG; Q1, TG≤0.92 mmol/L), the risk of TNs was 45% (OR＝1.45, 95%CI 1.06-1.98) higher for those in Q2 (TG 0.93-1.24 mmol/L), 101% (OR＝2.01, 95%CI 1.47-2.77) higher for those in Q3 (TG 1.25-1.81 mmol/L), and 67% (OR＝1.67, 95%CI 1.19-2.33) higher for those in Q4 (TG>1.81 mmol/L) after adjusting for age, body mass index (BMI) and education. For each unit increase in log10TG, the risk increased by 98% (OR＝1.98, 95%CI 1.14-3.45). Moreover, the correlation remained statistically significant even after further adjustment for thyroglobulin antibody (TGAb), thyroid peroxidase antibody (TPOAb) and urinary iodine (OR＝1.75, 95%CI 1.00-3.06, P＜0.05). However, correlations of total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C) and low-density lipoprotein cholesterol (LDL-C) with the risk of TNs were not statistically significant. Restricted cubic spline regression analysis further demonstrated the non-linear dose-response relationship of TG levels with the risk of TNs. Specifically, the risk of TNs increased in a monotonic manner at lower TG concentrations (＜1.23 mmol/L), but appeared to plateau or even slightly decrease at higher levels of TG (≥1.23 mmol/L). ConclusionsAmong euthyroid women, higher serum TG level is associated with risk of TNs, and this correlation is non-linear.